The macroscopic and microscopic patology changes on broiler infected with local reovirus isolate - Sutiastuti Wahyuwardani; Hernomoadi Huminto; Lies Parede (Indonesian Center for Animal Research and Development (ICARD), 2005)
Local reovirus isolate is the virus which could be isolated from runting and stunting syndrome. The ability of local reovirus isolate to induce runting and stunting syndrome in broilers chicken was investigated. The day old chicks (doc) were infected with local reovirus isolate assessed clinically and pathologically at 1, 2 and 3 weeks post inoculation. A total of 40 DOC were divided into two groups. The first group (20 doc) was orally infected with ± 2 x 103 local reovirus isolate particle and the other used as negative control group. The results showed that the isolate caused wet droppings, stunting, enteritis, pancreatitis, malabsorbtion, bursal atrophy and spleenic hypertrophy, which similar to runting and stunting syndrome (RSS) disease in chicken. The body weight was reduced to 14.7% on the inoculated group at 4 weeks post inoculation. Key Words: Broiler, Local Reovirus Isolate, Runting and Stunting, Malabsorption